2022
DOI: 10.3390/en15155721
|View full text |Cite
|
Sign up to set email alerts
|

Low-Carbon Supply Chain Decisions Considering Carbon Emissions Right Pledge Financing in Different Power Structures

Abstract: While carbon emissions reduction brings about environmental benefits, it can also create financial pressure on many manufacturing enterprises. Many manufacturing enterprises have begun to pledge their own carbon emissions right quotas for financing and the funds from this financing are being used to implement energy savings and emissions reduction strategies. To investigate the impact of carbon emissions right pledge financing on supply chains, this study constructed a two-echelon low-carbon supply chain, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…However, when we compare the role of members in both the previous investigated papers and Section 2, either the manufacture is acting as the bellwether or the retailer is dominating, this configuration is recognized as power structure (Li et al, 2022). Noticeably, there is no Stackelberg model used in the trade-off mechanism and two players choose their strategies simultaneously.…”
Section: Comparison Between Cost-revenue Sharing Contract and Trade-o...mentioning
confidence: 99%
“…However, when we compare the role of members in both the previous investigated papers and Section 2, either the manufacture is acting as the bellwether or the retailer is dominating, this configuration is recognized as power structure (Li et al, 2022). Noticeably, there is no Stackelberg model used in the trade-off mechanism and two players choose their strategies simultaneously.…”
Section: Comparison Between Cost-revenue Sharing Contract and Trade-o...mentioning
confidence: 99%
“…Wang et al [40] combined the order fnancing model in green fnance and found that a carbon tax and green fnance can promote the green transformation of corporate clean technologies. Li et al [41] constructed a two-echelon lowcarbon supply chain model wherein the manufacturer is capital-constrained to use carbon pledge fnancing and analyze the manufacturer's CER decisions and supply chain members' profts under diferent power structures. Furthermore, some scholars have designed contracts to coordinate cash-constrained supply chain members.…”
Section: Low-carbon Supply Chain With Capital Constraintsmentioning
confidence: 99%